Role of anti-reflux mucosal ablation in “reflux-predominant” refractory gastro-esophageal reflux disease patients - a randomized sham controlled trial - Chavan, Digvijay; Koduri, Krithi Krishna; Singh, Aniruddha Pratap; Maragoni, Rajesh Goud; Jagtap, Nitin; Kalapala, Rakesh; Reddy, Nageshwar D. (Endoscopy)
Background & Aim Refractory gastroesophageal reflux disease(GERD) often requires endoscopic or surgical intervention. This randomised controlled trial(RCT) evaluated the efficacy of anti-reflux mucosal ablation(ARMA) compared to sham in patients with “reflux-predominant” refractory GERD. Methods: This single-center, randomized, sham-controlled trial enrolled patients with persistent GERD symptoms on optimized PPI therapy, with Acid Exposure Time(AET) <6%, and >80 reflux episodes on 24-hour-pH-impedance monitoring. Patients were randomized to ARMA or sham group. The primary outcome was proportion of patients achieving 50% improvement in GERD health-related quality-of-life(GERD-HRQL) score from baseline toat 6 months. Secondary outcomes included heartburn and regurgitation symptom scores, AET, DeMeester score, reflux episodes, endoscopy findings, and PPI consumption. Mixed-effects models were applied with group(ARMA vs. sham) as a fixed effect and participant as random effect. Results: Fifty-eight patients(ARMA: n=28, median age 41, 32.1% female; Sham: n=30, median age 40, 35.7% female) were included. Baseline mean PPI-use duration was similar(ARMA:3.5±2.7 years, Sham: 3.7±1.8 years). At 6 months, 20(71.4%) of ARMA patients achieved ≥50% GERD-HRQL score reduction vs. 1(3.6%) in sham(p<0.001). Statistically Ssignificant reductions in heartburn, regurgitation, AET, and reflux episodes were seen in ARMA compared to sham(p<0.05). Interaction effects revealed greater improvements over time in ARMA group compared to sham for AET(p=0.029), total reflux episodes(p=0.001), and non-acid reflux episodes(p=0.009), not for DeMeester score(p>0.05). The ARMA group, had significant improvement in endoscopic Hill’s grading and esophagitis at 6 months and 35.7% patients were completely off PPIs. Conclusion: ARMA significantly improves symptoms, AET, and reflux episodes in “reflux predominant” PPI-refractory GERD.